2006
DOI: 10.1097/01.inf.0000202065.03366.0c
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Analysis of Meningococcal Disease Mortality in the United States

Abstract: Meningococcal disease continues to be an important, vaccine-preventable cause of death in the United States. Vaccination and other disease prevention efforts should be augmented for higher risk groups. Meningococcal mortality data can be used to assess the effectiveness of these efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…However, a reasonable amount of indirect evidence from several continents exists. In the United States, those with darker skin have increased risk (Sharip et al, 2006), and rates are highest in winter and lowest in summer (Kinlin et al, 2009;Sharip et al, 2006). Because meningitis is linked to bacterial infections, and vitamin D reduces the risk of bacterial infections through induction of cathelicidin and defensins (Gombart, 2009), one can reasonably expect vitamin D to reduce the risk of meningitis.…”
Section: Meningitismentioning
confidence: 99%
“…However, a reasonable amount of indirect evidence from several continents exists. In the United States, those with darker skin have increased risk (Sharip et al, 2006), and rates are highest in winter and lowest in summer (Kinlin et al, 2009;Sharip et al, 2006). Because meningitis is linked to bacterial infections, and vitamin D reduces the risk of bacterial infections through induction of cathelicidin and defensins (Gombart, 2009), one can reasonably expect vitamin D to reduce the risk of meningitis.…”
Section: Meningitismentioning
confidence: 99%
“…Although significant advances have been made in the development and coverage of vaccines, the disease burden remains high, highest in the meningitis belt in subSaharan Africa, where epidemics occur in waves lasting 3 to 4 years, the last in 2009 (64). Due to the immaturity of the immune system and decline of maternal antibodies (Abs), the incidence of meningococcal disease peaks in the first year of life, although it varies between countries due to differences in serogroup distributions (21,30), and mortality is highest in infancy and for teenagers (50). Thus, it is of utmost importance to design early-life vaccination strategies that induce protective immunity in early infancy as well as long-lasting immunological memory against these major pathogens.…”
mentioning
confidence: 99%
“…Remarkably, no Norwegian infants below 1 y of age died (which corresponds to two infants in our material). A study from Iceland identified age but not gender as a risk factor [27] while a study from the USA found that infants, adolescents (aged 15Á24 y) and elderly adults over 74 y were risk factors, whereas gender was not [28]. Yazdankhah et al [29] found that the distribution of meningococcal isolates varies temporally and geographically.…”
Section: Discussionmentioning
confidence: 95%